Problem solving methods of clinical clerks in the De La Salle University Health Sciences campus - Adiviso, Shirard Leonardo C.
Specific decisions in managing the patient necessitates an organized approach to gathering of information and a systematic approach to evaluation of that information and formulation of treatment plans. At De La Salle University Health Sciences Campus (DLSU-HSC) Department of Surgery, faculty members have noted that residents, interns and students have difficulty relating the clinical presentation to patient's illness. A great majority failed to synthesize the available data into diagnosis. There are many reasons why medical students fail to utilize problem-solving skills in their daily activities. These include long curriculum hours, too much didactic teaching, excessive lectures with little problem-solving activities, no student responsibility for mastering lower order thinking skills, training students who only want predigested facts, uncooperative faculty, and resistance to change. The objective of the study is to determine the different problem-solving methods utilized by the clinical clerks at De La Salle University Health Sciences campus. The researcher utilized several questionnaires and a series of focus group interviews of hypothetical and actual case scenario of most common surgical diseases encountered by the twenty clinical clerks during their rotation in General Surgery from April to May 2002. The results of the study revealed that the clinical clerks only utilized four kinds of problem-solving methods. The three, namely: traditional, early hypothesis generation and forming differentials are established methods from the review of literature. The last one is labeled unclassified since it is not similar to any one of the known methods. The study also showed that majority of the students would like to have problem-solving skills taught during the early years of medical education, which should be handled by the clinical faculty. The study also revealed that problem-solving skills are learned from the preceptors and mainly in the Department of Surgery and Medicine. They also believed that small group learning activities and problem-oriented lectures enhanced the development of problem-solving skill. However, they perceived that the present curriculum does not develop problem-solving skills. Thus, they proposed changes like shifting to Problem Based Learning, utilizing case problems, discussing in small groups and giving constructive criticism to develop problem-solving skills among students. Medical students do not automatically develop problem-solving skill. This should not be left to chance. This basic skill should be taught properly and utilized frequently to achieve expertise. The students also demonstrated a superficial level of competency in engaging in more complex thinking skills. This may be due to their lack of mastery of the lower order cognitive skills. Based on the results of the study, the following are recommended: 1) that volunteer faculty members undergo training sessions in teaching problem-solving skills and methods; 2) that problem-oriented or case-based lectures using principles of small group learning be conducted; 3) that the faculty will not only concentrate on factual data, but also on the process of thinking during preceptorials; 4) that Objective Structured Clinical Examination (OSCE) as an assessment scheme to develop more problem-solving skills instead of sole written evaluations be adapted; 5) that medical students achieve mastery of lower order thinking skills in order to develop more complex cognitive skills.